In patients with multi-vessel coronary artery diseases, does hybrid revascularization provide similar outcomes to conventional coronary artery bypass grafting?. (7th May 2021) - Maskell, Perry; Graham, Catherine; Roberts, Lydia; Harky, Amer
Summary: A best evidence topic in cardiac surgery was written according to a structured protocol. The question addressed was: In [patients with multivessel coronary artery diseases (CAD)] is [hybrid revascularization (HCR)] equal to [coronary artery bypass grafting (CABG)] in regard to [mortality, myocardial infarction, stroke and target vessel revascularization (TVR)]? Three-hundred and fifty-five papers were found using the reported search, of which 8 represented the best evidence to answer the question. The authors, journal, date and country of publication, patient group studied, study type, relevant outcomes and results of these papers are tabulated. The studies included 4 observational studies, 3 randomized controlled trials (RCTs) and 1 meta-analysis. The meta-analysis consisted of predominantly observational data with 1 randomized controlled trial and suggested non-significant differences in all major clinical outcomes. The observational studies generally cited benefit towards hybrid revascularization on the basis of equivalent major clinical outcomes rates compared to coronary artery bypass grafting, yet favourable in-hospital outcomes. One randomized controlled trial provided robust evidence of equivalent 5-year outcomes; however, the others were insufficiently powered for an effective comparison. There is a paucity of robustly designed studies to answer our clinical question effectively, given hybrid procedures are not routine in clinical practice. On the basis of mostly observational and small randomized cohorts with relatively short follow-up intervals, we conclude that current evidence suggests similar mid-term rates of major clinical outcomes after hybrid revascularization and coronary artery bypass grafting. However, without longer-term follow-up, the comparison of the two techniques, particularly relating to repeat revascularization, is still very much uncertain.